Evaluasi program penyediaan air minum dan sanitasi berbasis masyarakat (PAMSIMAS): studi di Kabupaten Temanggung - Puspita, Dhestiane Sherly; Kawuryan, Istiarsi Saptuti Sri; Handayani, Widhi (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2023)
Population growth has an impact on land use change which leads to various environmental issues, including the clean water needs. The Community-Based Drinking Water and Sanitation Provision (PAMSIMAS) is one of the government's programs aimed at fulfilling the clean water and sanitation needs of community. Although there are still implementation problems, this program has shown positive benefits and impacts in various regions. This research aims to explain the achievements of the PAMSIMAS program in Temanggung Regency as a government effort to improve the people welfare. This is a quantitative study using secondary data and analyzed using descriptive analysis. The results of the research show that the realization of PAMSIMAS in Temanggung Regency for drinking water is considered good, with the lowest being around 75%, and some achievements exceeding the target of 100%. PAMSIMAS realization for sanitation is still fluctuating with low sanitation realization in three sub-districts, namely Bansari sub-district (27.13%), Wonoboyo sub-district (8%), and Tretep sub-district (6%). The low level of sanitation is caused by the low economic status, weak social norms, and weak social capital. Further studies are needed to find the factors causing the low sanitation realization in these sub-districts in order to find the best solution.